(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study delves into the intricate dynamics of brand loyalty in the evolving landscape of the subscription economy, with a specific focus on the influential factors shaping consumer loyalty in Netflix compared to other Over-The-Top (OTT) platforms. The primary objectives of the research are to analyse the impact of subscription services on consumer loyalty, with a nuanced exploration of three critical aspects: Value Proposition, Content Quality & Interface, and Incentives and Rewards.To achieve these objectives, a rigorous research methodology was employed, involving a primary survey conducted through social media platforms. The survey utilized a structured questionnaire, incorporating a 10-point scale to rate consumer perceptions on the aforementioned aspects. A selective sampling strategy was applied, targeting 20 subscribers of Netflix and 20 subscribers of other OTT platforms, ensuring representation from active users. The statistical analysis was conducted using MS-Excel, employing an Independent Sample t-test to discern significant differences in Consumer Loyalty between the two groups.The results revealed noteworthy insights. There was a significant disparity in Consumer Loyalty between Netflix and Other OTT Platforms concerning the Value Proposition and Content Quality & Interface. Netflix exhibited lower mean values and higher standard deviations, indicating comparatively lower and more variable Consumer Loyalty scores. In the case of Incentives and Rewards, the results were on the borderline of significance, suggesting a potential difference in the influence of these programs on Consumer Loyalty.Based on these findings, strategic recommendations are proposed to enhance consumer loyalty for Netflix. These include refining the Value Proposition to offer a clear advantage over competitors, optimizing Content Quality & Interface for a superior user experience, and fine-tuning Incentives and Rewards programs. The study advocates for continuous consumer feedback, competitor benchmarking, and personalized strategies to stay attuned to evolving consumer preferences.